PARADIGMA DAKWAH MODERASI BERAGAMA DI MEDIA SOSIAL - Mubarok, Agus (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2023)
This research aims to reveal the important role of da'wah in spreading the concept of religious moderation in religious life on social media. The method used in this research is library research with a qualitative approach. So that a strong theoretical foundation is obtained in analyzing how the concept of religious moderation is applied in the context of social media, as well as how da'wah can play an important role in spreading the message of religious moderation on social media. The study results show that da'wah plays a central role in communicating religious moderation in the context of religious life. Analysis of Google search trends with keywords such as “religious moderation,” “Islamic Moderation,” “Islam Wasatiyah,” and “Dakwah” indicates significant interest in issues of moderation and religion on social media. The conclusion of this research shows that the strategy of preaching religious moderation on social media has great potential to address issues of radicalism, intolerance and extremism. This research can have implications for opening the mindset of the religious moderation preaching paradigm on social media as well as becoming a concept that corrects wrong understanding in religious life.